Effect of Nitrogen on Weed Infestation and Performance of Boro Rice Under Two Selected Herbicides (Bangladesh Agronomy Journal, 2016)
A field experiment was conducted at the experimental farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Salna, Gazipur from November 2013 to May 2014 to determine the effect of nitrogen and herbicide on weed infestation and performance of Boro rice (cv. BRRIdhan28). Five nitrogen doses i.e. 0 , 50.6 , 101.2 , 151.8 and 202.4 kg ha-1 under selected pre-emergence and post-emergence herbicides along with one weed free and control (unweeded) treatment were imposed in the experiment. Nine weed species was found to dominate in the experimental plots where Scirpus maritimus L. showed the maximum visual abundance (58%) followed by Leersia hexandra sw., Paspalam distichum L. and Fimbristylis miliacea L. Post-emergence herbicide contributed to higher control efficiency than that in pre-emergence herbicide. Post-emergence herbicide without receiving nitrogen showed the highest weed control efficiency (97.39) at 60 days after transplanting. Treatment receiving N @ 200.4 kg ha-1 under post-emergence herbicide showed the highest number of tiller per hill (13.00), total dry matter (1568.6 g m-2), panicles per hill (10.60), filled grains per panicle (125.20) and grain yield (6.46 t/ha). N-dose 151.8 kg ha-1 under postemergence herbicide contributed to the second highest grain yield (6.41 t ha-1) with the highest benefit cost ratio of 1.60 but 50.6 kg N ha-1 under post-emergence herbicide showed the maximum Nitrogen use efficiency of 0.49. The study revealed that nitrogen dose up to 151.8 kg ha-1 might be increased above the recommended dose under coverage of a suitable post-emergence herbicide for profitable rice production.Bangladesh Agron. J. 2015, 18(2): 53-63